COMMISSIONING TESTING FOR IN VITRO IN VIVO FACILITY AT RADIAL PIERCING BEAM-PORT OF THE KARTINI RESEARCH REACTOR FOR BORON NEUTRON CAPTURE CANCER THERAPY - Widarto Widarto (Indonesian Journal of Physics and Nuclear Applications, 2019)
The purpose of the commissioning for in vitro in vivo test facility is to verify that the the facility has fulfilled the safety standards requirements, especially those related to radiation exposure. The standard requirement for environmental radiation exposure by IAEA is 20 mSv/hour. Otherwise results of the premilinary commissioning testing at the distance of 3 meters from in vitro in vivo test facility at radial piercing beam-port for 100 kW power level of the Kartini research reactor is for radiation exposure being around 9 mSv/hour. This means that the radiation exposure is less than the IAEA safety standard requirement of 20 mSv/hour. This is also less than the requirement of The Indonesian Regulatory Body limitation which is restricted to 15 mSv/hour. It can be concluded that when the reactor is operated at 100 kW power level for utilization by experiments in vitro/in vivo test, the facility is safe. However in order to be more safe at the restricted area, implementation of total quality management system should be completed with standard operating procedure (SOP) conducted with distance, time and shielding of radiation exposure for radiation safety protection system in utilization of the in vitro in vivo test facilities. When the SOP of the utilization of the in vitro in vivo test facility is implemented, the procedure is safer.